((x+5)/3)=((x-2)/-4)

Simple and best practice solution for ((x+5)/3)=((x-2)/-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ((x+5)/3)=((x-2)/-4) equation:


x in (-oo:+oo)

(x+5)/3 = (x-2)/(-4) // - (x-2)/(-4)

(x+5)/3-((x-2)/(-4)) = 0

(x+5)/3+(-1*(x-2))/(-4) = 0

(-4*(x+5))/(-4*3)+(-1*3*(x-2))/(-4*3) = 0

-4*(x+5)-1*3*(x-2) = 0

-7*x-14 = 0

(-7*x-14)/(-4*3) = 0

(-7*x-14)/(-4*3) = 0 // * -4*3

-7*x-14 = 0

-7*x-14 = 0 // + 14

-7*x = 14 // : -7

x = 14/(-7)

x = -2

x = -2

See similar equations:

| 5(-6x+8)=-110 | | 1/10/1/2 | | y=x^2-5+6 | | U/9=-12 | | 11x--9=-13 | | 2(3x+3)=18 | | (x/3)/2x-1 | | 3x-6/14 | | 5n-3=8-6n | | ((x+2)/3)=(-1/5) | | 5xy-10= | | -2+4x=x-23 | | 4y+7-7=10+3y | | B=3(v/h) | | -7(6x+8)=-182 | | -2a+a-5+10= | | 6x^4+6x^3-36x^2=0 | | 4p+6=60 | | -2a+15=2a+5z | | 2/3t-11=4(6-t)-1/3t | | j+.333333=.75 | | 12-45= | | 12x=280+4x | | 6y+12=4y+4 | | -7(6x-1)=-27-8x | | (X+12/x+2)-3=0 | | 5x+8=-x-40 | | 8.9=9.5-0.2x | | 16x^2+-5(7-x^2)+43=0 | | 66x+5=180 | | 3(8-6x)=96 | | 44/7/d=4/7 |

Equations solver categories